Flexural characteristics of additively manufactured continuous fiber-reinforced honeycomb sandwich structures - Rafael Guerra Silva; Gustavo Morales Pavez (Composites Part C: Open Access)
Additive manufacturing of continuous fiber filament is an advanced process that combines continuous strands of reinforcing fibers with thermoplastic materials to create composite parts. Previous studies have explored the potential of this technology to produce solid composite materials, but its potential for the production of sandwich panels has been limited. For instance, continuous fiber can be used to reinforce the faces while lightweight customized lattice structures could be selected for the core, all built integrally in one single process. This study analyzes the effect of reinforcement material and fiber orientation on the flexural behavior of continuous fiber-reinforced sandwich structures built entirely using a commercially available fused filament fabrication printer. Three-point bending tests were carried out on sandwich panel specimens, which were built using nylon reinforced with chopped carbon fiber and two reinforcement fibers, glass or carbon fiber. The carbon fiber-reinforced sandwich panels had a higher rigidity than those reinforced with glass fiber, but carbon fiber showed significant scattering. Additionally, we explored the influence of fiber content on the flexural behavior of the composite sandwich panels. As predicted by the theoretical models, a higher fiber content led to higher values of flexural modulus and strength. The analytical models were able to predict the flexural modulus and critical load with a relative error of approximately 20 % for low fiber volume fraction in the facing. On the other hand, in carbon fiber-reinforced specimens, when doubling the fiber volume fraction in the facing, the relative error was above 60 %.